2014
DOI: 10.1021/jp509708t
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Behavior of Eutectic LiBH4–Mg(BH4)2 and Its Confinement Effects in Ordered Nanoporous Carbon

Abstract: We present the crystal structure, diborane (B 2 H 6 ) and triborane (B 3 H n ) evolution, and dehydrogenation kinetics, of both bulk and nanoconfined Li/Mg(BH 4 ) 3 in a highly ordered nanoporous carbon template. The bialkali borohydride Li/Mg(BH 4 ) 3 mainly forms a structure similar to that of α-Mg(BH 4 ) 2 . The decomposition temperature of Li/Mg(BH 4 ) 3 lies between that of LiBH 4 and Mg(BH 4 ) 2 . A direct line-of-site residual gas analyzer mass spectrometer shows that very little diborane and no detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…[189][190][191] In one case, the eutectic LiBH 4 -Ca(BH 4 ) 2 was successfully infiltrated into mesoporous carbon, and the positive effects of nanoconfinement were observed through the enhanced hydrogen desorption and absorption properties, improving the hydrogen storage performance of the device. With this, the effects of confinement and the interaction between the template pattern and the solidifying eutectic (for surface-selective nucleation) can be combined to tailor the assembly of the phaseseparating components.…”
Section: Template-directed Solidification Of Eutectic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[189][190][191] In one case, the eutectic LiBH 4 -Ca(BH 4 ) 2 was successfully infiltrated into mesoporous carbon, and the positive effects of nanoconfinement were observed through the enhanced hydrogen desorption and absorption properties, improving the hydrogen storage performance of the device. With this, the effects of confinement and the interaction between the template pattern and the solidifying eutectic (for surface-selective nucleation) can be combined to tailor the assembly of the phaseseparating components.…”
Section: Template-directed Solidification Of Eutectic Materialsmentioning
confidence: 99%
“…To infiltrate LiBH 4 into porous materials, it was helpful to form eutectic mixtures, as this decreases the melting point and thus the required temperatures for melt infiltration. [189][190][191] In one case, the eutectic LiBH 4 -Ca(BH 4 ) 2 was successfully infiltrated into mesoporous carbon, and the positive effects of nanoconfinement were observed through the enhanced hydrogen desorption and absorption properties, improving the hydrogen storage performance of the device. [189] Perhaps not surprisingly, it has been observed that the nanoconfinement of eutectic materials within a porous template leads to slight modifications in the phase diagram and melting characteristics as interaction between the eutectic melt and the template surface changes the overall thermodynamics of the system.…”
Section: Template-directed Solidification Of Eutectic Materialsmentioning
confidence: 99%
“…. Many eutectics are formed at a different molar fraction composition, from a temperature as low as 105 °C for 0.725LiBH 4 ‐0.275KBH 4 ,, 216 °C for 0.70LiBH 4 ‐0.30NaBH 4 ,, 150 °C for 0.55LiBH 4 ‐0.45Mg(BH 4 ) 2 , and 200 °C for 0.68LiBH 4 ‐0.32Ca(BH 4 ) 2 ,. In binary combinations without LiBH 4 , thermal minima or partial melting have been observed, at 462 °C for 0.682NaBH 4 ‐0.328KBH 4 , 205 °C for 0.40NaBH 4 ‐0.60Mg(BH 4 ) 2 , and above 350 °C for the NaBH 4 ‐Ca(BH 4 ) 2 system .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of cationic solid solutions in binary borohydrides are limited to the Mg(BH 4 ) 2 -Zn(BH 4 ) 2 [170], Mg(BH 4 ) 2 -Mn(BH 4 ) 2 [28], LiBH 4 -NaBH 4 [152] and NaBH 4 -KBH 4 [27] systems. In other cases, a nearly full immiscibility is observed [153,156,[186][187][188][189][190][191][192], suggesting structural and electronic constrains in the formation of solid solution in cationic sublattice in the case of borohydrides. Considering the LiBH 4 -NaBH 4 -KBH 4 system, LiBH 4 can form a cubic phase with limited solid solubility in NaBH 4 and KBH 4 .…”
Section: Solid Phasesmentioning
confidence: 99%